ORGANIZATION GOAL-ORIENTED REQUIREMENTS ENGINEERING IN INFORMATION SYSTEM DEVELOPMENT - Adikara, Fransiskus
Requirements engineering phase is one of important process in information system development. There are risk of uncertainty things that may arise in requirements engineering phase if the system requirements based on and derived from user requirements. Based on this background, it takes a requirements engineering methods to reduce the impact of of these uncertainties. Nowadays, the requirements engineering methods have been transform and use goals as a reference in the information system requirements engineering process. This research develop and improve Goal Oriented Requirements Engineering / GORE methods in order to reduced the uncertainties that may arise because of the users requirements, and can effectively use the solution of preexisting requirement in engineering processes. The new requirements engineering methods using the organization goals as the primary source of information system requirements and the goals have measurements in the form of Key Performance Indicator (KPI) to control the uncertainties that may arise from the users interest, so the information system requirements can be obtained without depending on the end users requirements. Beside that, the new requirements engineering method also adapting the Case- Based Reasoning (CBR) method to be able to reuse preexisting requirements as a solution to improve the quality of system requirements and accelerate the process engineering requirements. The new requirements engineering method have been develop using existing components from preexisting GORE methods and also adapting other methods and techniques beside GORE research. There are two case studies conducted in this study with purpose to see new GORE implementation results of the new requirements engineering methods and the requirements engineering results have been useing in the further information system development process to evaluate the requirements fulfillment by information system functions. The new requirements engineering process quality have been evaluated and compared with preexisting GORE methods using assessment methods of COncern of Requirements Engineering (CORE). The outcome of these case study have demonstrate that the new GORE process may use the organization goal as primary source of the information system requirements without relying on end users' requirements. Key Performance Indicator that used as measuring tool can control and reduce the uncertainty that arises because of the user's interest. Adaptation of CBR method to reuse preexisting requirements as solution can also increase the speed and effectiveness of the requirements engineering process. Based on this method, the information system requirements can be automatically obtained using parameters acquired from the organization's goals and utilize the existing case-based without relying again with the uncertainties of users requirements. With this automation process, it is expected that the requirements engineering process can take place quickly and already has a specific template for the organization needs (and become case-based for reuse). In the future, the organization owners and the company board of directors can have and develop a quality information system simply by only having organizational goals using this methods.